Real-World Clinical Outcomes of Low Dose versus Standard Dose Abiraterone in Patients with Metastatic Castration-Resistant Prostate Cancer: A Prospective Pragmatic Study - Razmjoo, Sasan; Hosseini, Seyed Mohammad; Bagheri, Ali; Feli, Maryam; Karimi, Faride (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Abiraterone is a standard treatment for metastatic castration-resistant prostate cancer (mCRPC). Food intake has shown significant effect on its pharmacokinetics. The aim of this study was to evaluate the efficacy and safety of standard dose abiraterone under fasting conditions versus low dose abiraterone with a low-fat meal in patients with mCRPC. Methods: In this prospective real world study 32 patients with mCRPC were treated in two groups of 16 cases by routine clinical practice of their treating physician with low-dose abiraterone (250 mg with a low fat breakfast) or standard-dose abiraterone (1000 mg in fasting state). The changes in serum prostate specific antigen (PSA) level and PSA response rate (≥50% reduction after 12 weeks) were the primary end points. Results: The median changes of serum PSA before and after treatment, as well as the PSA nadir were not significantly different between the two groups (P = 0.128 and P = 0.051, respectively). Despite a trend toward higher PSA response rate in the low-dose group, the difference was not statistically significant (75.0% vs. 62.5%; P = 0.704). Median serologic progression free survival (PFS) was significantly higher in the low-dose group (15 vs. 8 months; Log-rank P = 0.031). There was a trend toward lower adverse events in the low-dose group, but this difference was not statistically significant (37.5% vs. 62.5%; P = 0.289). Conclusion: Low-dose abiraterone seems to be comparable to standard-dose abiraterone in mCRPC with 75% lower financial cost; however, this conclusion needs to be proved by further well designed and large scale studies.